Symptomatic versus asymptomatic pyeloplasties: A single institution review - Metcalfe, Peter; Assmus, Mark; Kiddoo, Darcie (Canadian Urological Association Journal, 2014)
Introduction: Historically, pyeloplasties have been performed after symptoms and radiographic confirmation of an ureteropelvic junction obstruction (UPJO). However, with prenatal ultrasonography, the approach to patients has fundamentally changed. Increasingly, patients are diagnosed and treated before the advent of morbidity, based on imaging findings alone. However, optimum screening strategies and thresholds for intervention vary significantly, are controversial, and are not founded on outcome-based evidence. We examined all pyeloplasties performed at our institution and reviewed their indication for surgery. We hypothesized that, despite ubiquitous screening for UPJO, most pyeloplasties had been performed secondary to symptoms and did not benefit from antenatal screening. Methods: A retrospective chart review was performed of all pyeloplasties performed at the Stollery Children’s Hospital, Edmonton, Alberta, over the past 8 years. Patients were categorized according to indication for surgery: symptomatic or asymptomatic. Results: Most (60%) of our pyeloplasties were performed for symptomatic indications. Furthermore, 12% of these patients had antenatally detected hydronephrosis that was thought to have resolved spontaneously during follow-up. Of our symptomatic patients, 37% were undergoing surveillance with the expectation for spontaneous resolution. Of the 29 patients who underwent pyeloplasty, 8 suffered a preoperative loss of function on renal scans; however, only 50% returned to within 90% of their original function. Conclusion: Despite active surveillance of antenatally detected hydronephrosis, most pyeloplasties at our institution were performed for de-novo symptoms. We believe that this simple observation reinforces that our current surveillance strategies are unable to predict and eliminate all morbidity from UPJO.